Structure of a left-handed DNA G-quadruplex - Chung, Wan Jun (2015)
Aside from the well-known double helix, DNA can also adopt an alternative four-stranded structure known as G-quadruplex. Implications of such a structure in cellular processes, as well as its therapeutic and diagnostic applications, have been reported. The G-quadruplex structure is highly polymorphic, but so far, only right-handed helical forms have been observed. Here we present the NMR solution and X-ray crystal structures of a left-handed DNA G-quadruplex. The structure displays unprecedented features that can be exploited as unique recognition elements.